2019
DOI: 10.1096/fj.201801381rr
|View full text |Cite
|
Sign up to set email alerts
|

Spleen iron, molybdenum, and manganese concentrations are coregulated in hepcidin‐deficient and secondary iron overload models in mice

Abstract: Iron excess increases the hepatic expression of hepcidin, the systemic iron metabolism regulator that favors iron sequestration in the spleen. Genetic iron overload related to hepcidin insufficiency decreases the spleen iron concentration and increases hepatic iron concentration, whereas during secondary iron overload, the hepcidin expression increases together with spleen iron concentration in addition to hepatic iron concentrations increase. Links between iron metabolism and other metals being suggested, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The parenteral iron supplementation that we performed in mice has been previously shown to lead to an iron overload in both parenchymal cells and macrophages. 26,27 In accordance to these data, we report blood iron parameters in iron-treated mice close to those observed in hereditary haemochromatosis patients (i.e. transferrin saturation >55%, serum iron levels >27 μmol/L, and liver iron content >8000-10 000 μg/g).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The parenteral iron supplementation that we performed in mice has been previously shown to lead to an iron overload in both parenchymal cells and macrophages. 26,27 In accordance to these data, we report blood iron parameters in iron-treated mice close to those observed in hereditary haemochromatosis patients (i.e. transferrin saturation >55%, serum iron levels >27 μmol/L, and liver iron content >8000-10 000 μg/g).…”
Section: Discussionsupporting
confidence: 88%
“…23,24,32 However, experimental protocols used in those studies induced a systemic and muscle iron overload largely beyond the classical findings observed in pathophysiological conditions. Here, we used an experimental murine model iron overload, 26,27 which involved injecting a unique dose of iron dextran to animals (1 g/kg), corresponding to an absolute dose of iron range from 25 to 35 mg. Four months after the injection, we reported a clinical picture of a high iron overload with blood parameters similar to those observed in humans. 42,43 On contrary, Reardon et al injected iron dextran several times over a month to a total of dose of 200 mg, 24 whereas Ikeda et al injected a total of 140 mg in only 2 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As hepcidin controls iron release from cells, especially spleen macrophages, it could play a key role in microgravity‐induced iron misdistribution by limiting the expression and activity of ferroportin, the cell iron exporter that allows iron recycling from macrophages in plasma 11 . Notably, it has been suggested that iron metabolism has strong interactions with other essential metals, especially due to the fact that some iron proteins could also participate in the metabolism of other metals 12‐16 . Except few data collected in astronauts during spaceflight, 17 the effects of microgravity on hepcidin regulation in humans remains poorly understood despite its major role as an integrative signal in the control of systemic iron metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Some trace elements with relatively low concentrations in human body have shown obvious anti-cancer and anti-oxidant effects in previous studies. For example, selenium (Se) and molybdenum (Mo) have been proved to be involved in reactive oxygen species generation and to play crucial role in functioning of antioxidant enzymes ( 11 , 12 ). However, significant higher levels of Mo in serum were found in breast cancer patients than controls in a Korean population ( 13 ).…”
Section: Introductionmentioning
confidence: 99%